Prey and nesting preferences of the alien wasp Isodontia mexicana (Hymenoptera, Sphecidae) in southern Germany - Sarah von Adelmannsfelden; Felix Fornoff (Journal of Hymenoptera Research)
Isodontia mexicana (Sphecidae) is a neozoic wasp in Europe. Since its first recording in France in the 1960s, it has spread throughout Europe and is now considered established. It preys on grasshoppers for its larvae but so far, there is little empirical evidence on the composition of prey species and the wasp’s preference for nest tube diameters from Europe. For further insights into prey and nesting preferences, we placed layer nests with 4 different cavity diameters in contrasting habitats in Southwest Germany. The wasp’s prey consisted of two grasshopper species, Oecanthus pellucens and Meconema meridionale. For O. pellucens, 80% of the prey found were female, for M. meridionale 52% and the mean body length of M. meridionale was 11.92 mm (SD = 0.95) and that of O. pellucens was 12.31 mm (SD = 1.02). The preferred cavity diameter for nests was 11 mm, with preference given to deeper cavities within the offered layer nest. The flexibility in prey species may reduce the threat for individual prey species populations, but may allow further spread of the Sphecid wasp. However, the preference for relatively large diameters reduces the expected competition risk with native bees below previous expectations.